Overexpression of a Pathogenesis-Related Protein 10 Enhances Biotic and Abiotic Stress Tolerance in Rice - Wu, Jingni (Plant Pathol J, 2016)
Pathogenesis-related proteins play multiple roles in plant development and biotic and abiotic stress tolerance. Here, we characterize a rice defense related gene named “jasmonic acid inducible pathogenesis-related class 10” (JIOsPR10) to gain an insight into its functional properties. Semi-quantitative RT-PCR analysis showed up-regulation of JIOsPR10 under salt and drought stress conditions. Constitutive over-expression JIOsPR10 in rice promoted shoot and root development in transgenic plants, however, their productivity was unaltered. Further experiments exhibited that the transgenic plants showed reduced susceptibility to rice blast fungus, and enhanced salt and drought stress tolerance as compared to the wild type. A comparative proteomic profiling of wild type and transgenic plants showed that overexpression of JIOsPR10 led to the differential modulation of several proteins mainly related with oxidative stresses, carbohydrate metabolism, and plant defense. Taken together, our findings suggest that JIOsPR10 plays important roles in biotic and abiotic stresses tolerance probably by activation of stress related proteins.